La localización de videojuegos. Propuesta didáctica para la clase de traducción. - Plaza-Lara, Cristina; Grau Lacal, Carmen (My University, 2018)
Video game localization has experienced a spectacular development over the last decade. This fact forces trainers to incorporate these contents in the Translation and Interpreting curricula. Therefore, in this paper, the competences of video game localizers will be approached in order to define the theoretical framework. Subsequently, a didactic proposal will be presented for the training of future localizers. This proposal consists of a dubbing and subtitling task, which will lead to a larger final project that includes the localization of a cinematic episode of a video game. To this end, the objectives, contents, methodology and evaluation methods will be explained and computer tools will be integrated as part of the translation task. This will promote contextualized learning and the application of knowledge in future professional jobs.
Keywords: Traducción - Programas de estudio; Videojuegos; Localización de videojuegos; Propuesta didáctica; Competencias del localizador de videojuegos